Effect of divergence angle of ejector nozzle on aerosolisation of powdered nanoparticles. Issue 7 (3rd May 2019) - Wu, Yiyang; Tu, Chengxu; Zhang, Zhengang; Yang, Meng; Bao, Fubing; Yin, Zhaoqin
ABSTRACT: A combined experimental-numerical study was performed to reveal the mechanisms of powdered SiO2 nanoparticle (NP) breakage and establish the relationship between the divergent angle (α) of a convergent-divergent (C-D) nozzle and nanoparticle size distribution. All distributions of aerosolised SiO2 NPs obtained through ejectors with varied α were identically log-normal and unimodal. As α increased (from 8° to 20°), there were identified decreases in Geometric Mean Distribution (GMD)(from 216 to 189 nm), mode diameter, and median diameter, while Geometric Standard Deviation (GSD) increased slightly (from 1.59 to 1.65). The parallel negative growth trends of D25 and D75, with slightly decreasing interquartile (D25–D75) ranges, indicated that an increase in α could result in a clear shift of Particle Sizes Distribution(PSD) towards smaller particle sizes. This implied that NP deagglomeration was strengthened and the ejector became more efficient as α increased. Three cross-sections including the C-D nozzle outlet (Section1 ), mixer tube inlet (Section2 ), and central section (Section3 ) were selected to estimate the influence of shear stress (|τ|) distribution in the ejector on NP aerosolisation. Increasing α hardly changed the location of the two inner peaks, but it significantly decreased the values of inner peaks and smoothened |τ| distributions. |τ| in Section2 with different α exhibited a flat bimodal distribution and the two outer steep peaks (from Section1 ) disappeared. For |τ0| = 0.5 and |τ0| = 1 Pa, the ratio of the |τ| distribution range of |τ| > |τ0| (0.5 Pa < |τ0|< 5 Pa) to the entire section span, η, increased significantly as α increased. The growth rate of η decreased apparently for |τ0| ranging from 2 to 4 Pa, but for |τ0| ≥ 5 Pa, η stopped growing in Section1 . The maximum value of |τ| exerted no significant influence on NP dispersion. The smoothness and flatness of the |τ| distribution determined whether the powdered NPs could experience enough shear aerodynamics and be dispersed thoroughly. This played a crucial role in NP aerosolisation. The mechanism of the effect of α on NP dispersion resulted in smooth and flat |τ| distributions. This helped expand |τ| distribution to increase the possibility of powdered NPs experiencing stronger shear flow as α increased.